Notary's Responsibility for Land Sale and Purchase Agreement Deeds (PPJB) that Result in Default - Satmoko Anggoro, Irawan; Suwondo, Denny (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze: 1) The Notary's responsibility for the deed of the Land Sale and Purchase Agreement (PPJB) which resulted in default. 2) Legal protection for parties who are harmed due to default in the implementation of the land PPJB made before a notary. This type of research is analytical descriptive research. The approach method in this research is sociological juridical. The type of data in this research is secondary data. The data collection method uses library techniques (document study). The analysis in this research is prescriptive. The results of the research concluded: 1) The Notary's responsibility for the deed of the Land Sale and Purchase Agreement (PPJB) which resulted in default, namely showing that the notary has legal, administrative, and moral responsibility for the legal consequences of the deed he made. Based on the decision, the notary was deemed negligent because he did not carry out his official obligations to act honestly, carefully, and impartially as regulated in Article 16 paragraph (1) letter a of the Notary Law. Therefore, the notary's responsibility in this case includes a legal obligation to restore the rights of the injured party, administrative responsibility for failing to maintain legal certainty, and moral responsibility for failing to be neutral in protecting parties acting in good faith. 2) Legal protection for parties who are harmed due to default in the implementation of the PPJB for land made before a notary is an effort by the state to guarantee certainty and justice for parties with good intentions. In the Decision of the Boyolali District Court Number 7/Pdt.G/2024/PN Byl, legal protection is provided to sellers who are harmed due to the buyer's default and the negligence of Notary/PPAT Sunarto, SH who continues to withhold the certificate even though the agreement has been null and void. Based on Philipus M. Hadjon's theory, legal protection in this case includes two forms, namely preventive and repressive. Preventive protection should be carried out by notaries through caution and clear legal explanations, while repressive protection is realized through court decisions that restore the rights of sellers. This case emphasizes the responsibility of public officials in maintaining legal certainty and substantive justice for parties with good intentions.